An overview on warranty cost modelling in two-dimensional warranty using neuro-fuzzy approach - Jamahir, Nur Izzati (2012)
In early study of manufacturing, warranty studies were mainly carried out by researchers in the legal profession and, thus, such articles appeared only in the law journals. Subsequently, warranty studies attracted researchers from such field as economics, accounting, management, marketing engineering, operations research and statistics. There are two types of warranty namely one-dimensional warranty, which is based on product usage or product age, and two-dimensional warranty which considers both product age and usage. This paper is mainly concerned about two-dimensional warranty. We applied neuro-fuzzy system approach of AI to optimize warranty cost and period. In this paper, neuro-fuzzy framework apply in warranty cost modelling is proposed.